Enamel composite board as well as preparation method and application thereof

Through sandblasting treatment and epoxy adhesive composite technology, the flatness and adhesive applicability of curtain wall enamel composite panels are solved, and enamel composite panels with high bond strength, weather resistance and flatness are achieved, expanding their application scope and economic value.

CN119567705AInactive Publication Date: 2025-03-07ZHEJIANG KAIER NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411769187.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to make the enamel composite panels on the curtain wall flat, and the adhesive contained in it is not suitable for the enamel composite panels on the curtain wall, especially in the case of sun and rain and environmental changes.

Method used

The surface roughness of the enamel steel plate and the backing aluminum plate is improved by sandblasting treatment, the glaze is sprayed and fired at high temperature, stacked and pre-formed, and composited with epoxy adhesive. The specific steps include the bonding of the enamel steel plate to the aluminum honeycomb core and the backing aluminum plate.

Benefits of technology

The bonding strength, weather resistance and flatness of the enamel composite panels are improved, making them not only suitable for interior decoration, but also widely used in architectural curtain walls, expanding the scope of application and improving economic value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119567705A_ABST
    Figure CN119567705A_ABST
Patent Text Reader

Abstract

The invention discloses an enamel composite board as well as a preparation method and application thereof. The preparation method specifically comprises the following steps: (1) carrying out sand blasting treatment, glaze spraying, high-temperature sintering, stacking placement and pre-pressing shaping on enamel steel plates; (2) the backing aluminum plate is subjected to sand blasting treatment; and (3) sequentially compounding the enameled steel plate, the aluminum honeycomb core and the backing aluminum plate by using an epoxy adhesive to obtain the aluminum honeycomb composite plate. The enamel composite board is excellent in performance, the bonding strength, the weather resistance and the flatness of the board are all remarkably improved, and the enamel composite board is suitable for interior decoration and can also be widely applied to building curtain walls, so that the application range of the enamel composite board is widened, and the economic value of the enamel composite board is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of curtain walls and enamel composite panels, and more particularly to an enamel composite panel and a preparation method and application thereof. Background Art

[0002] The curtain wall is the exterior wall of a building. It does not bear weight and is hung like a curtain, so it is also called a "curtain wall". It is a lightweight wall with decorative effects commonly used in modern large and high-rise buildings.

[0003] The enamel composite panel is mainly composed of three parts: enamel steel plate, aluminum honeycomb core and backing aluminum plate. It is not only beautiful and easy to clean, but also has good anti-rust performance. However, after the enamel composite panel is applied to the curtain wall, the traditional crimping process cannot make the curtain wall enamel composite panel flat due to the large plastic deformation inside the enamel composite panel after high-temperature sintering. Moreover, the curtain wall enamel composite panel has higher requirements for adhesives after being exposed to the sun and rain, high and low temperature environment changes, and the internal adhesive is not suitable for the curtain wall enamel composite panel.

[0004] Therefore, how to develop an enamel composite panel suitable for curtain walls is a problem that technical personnel in this field need to solve urgently. Summary of the invention

[0005] In view of this, an object of the present invention is to provide an enamel composite board and a preparation method and application thereof to solve the deficiencies in the prior art.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A method for preparing an enamel composite plate comprises the following steps:

[0008] (1) The enameled steel plate is sandblasted, sprayed with glaze, fired at high temperature, stacked, and pre-pressed;

[0009] (2) sandblasting the backing aluminum plate;

[0010] (3) The enameled steel plate, the aluminum honeycomb core and the backing aluminum plate are compounded in sequence using epoxy adhesive. Specifically, the enameled steel plate and the aluminum honeycomb core are first bonded with the epoxy adhesive, and then the aluminum honeycomb core and the backing aluminum plate are also bonded with the adhesive to obtain the enameled composite plate.

[0011] Furthermore, in the above step (1), the enameled steel plate is sandblasted until the roughness thereof is 1.5-1.7.

[0012] A further beneficial effect of adopting the above method is that the present invention improves the surface roughness of the bonding surface between the enameled steel plate and the backing aluminum plate through sandblasting, increases the contact area between the epoxy adhesive and the contact surface, and changes the line contact into body contact.

[0013] Furthermore, in the above step (1), the spraying thickness of the glaze is 100-150 μm.

[0014] A further beneficial effect of the above method is that the bonding surface of the enameled steel plate of the present invention is sandblasted and then sprayed with glaze, which not only improves the adhesion between the enameled steel plate and the glaze, but also improves the roughness of the enameled surface.

[0015] Furthermore, in the above step (1), the pre-pressing pressure is 2-3 MPa and the time is more than 10 minutes.

[0016] A further beneficial effect of the above method is that the present invention pre-presses and shapes the enameled steel plate before compounding, and can eliminate the internal stress generated by high-temperature sintering through static overload.

[0017] Furthermore, in the above step (2), the backing aluminum plate is sandblasted until the roughness thereof is 1.5-1.7.

[0018] A further beneficial effect of the above method is that the backing aluminum plate of the present invention is sandblasted before use, which not only removes the oxide layer of the backing aluminum plate, but also improves the surface roughness of the backing aluminum plate.

[0019] Furthermore, in the above step (3), the epoxy adhesive comprises component A and component B in a mass ratio of 2:1;

[0020] In terms of mass percentage, component A includes 30%-40% epoxy resin, 30%-40% modified epoxy toughening agent, 5%-10% core-shell toughening particles, 5%-10% active diluent, 1%-5% silane coupling agent, 0.5%-1% wetting dispersant and 15%-25% filler;

[0021] In terms of mass percentage, component B includes 30%-40% of polyamide, 10%-20% of modified amine, 1%-5% of accelerator, 0.5%-1% of wetting and dispersing agent and 30%-40% of filler;

[0022] The epoxy resin is at least one of NPEL-128, EPOKUKDO YD-128, NPEF-170, YDF-170, DEN 431 and NPPN 631;

[0023] The modified epoxy toughening agent is at least one of SL-102C-2, 102C-4H, 102C-4L, 102C-4T, 102C-4R, PD3604, PD3614, JEF-0211 and ERS-172;

[0024] The core-shell toughened particles are at least one of kanekaMZ100, kaneka MZ200, kanekaB-564 and kaneka M-701;

[0025] The active diluent is at least one of 1.4-butanediol diglycidyl ether, 1.6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, cardanol glycidyl ether and pentaerythritol tetraglycidyl ether;

[0026] The silane coupling agent is γ-glycidyl ether propyl triethoxysilane (KH560);

[0027] The wetting and dispersing agent is at least one of BYK-2151, BYK-163, EFKA-4010 and Silok 7631;

[0028] The filler is at least one of 150 mesh heavy calcium carbonate, 800 mesh light calcium carbonate, 1500 mesh talc, fumed silica and kaolin;

[0029] The polyamide is at least one of Versamid 140, WSCM-4140, D8140, Ancamide 2784, G-640, G-0930 and G-5022;

[0030] The modified amine is at least one of LT-477, SF-PAA-5035P, SF-PAA-4530, R-2269 and R-3611;

[0031] The accelerator is at least one of 2,4,6-tris(dimethylaminomethyl)phenol, 2-ethyl-4-methylimidazole, salicylic acid, triphenylphosphine and 1,8-diazabicycloundec-7-ene.

[0032] A further beneficial effect of the above is that the epoxy adhesive of the present invention has high heat resistance, high peel strength, and good heat and aging resistance, can be cured at room temperature of 25°C, and has good adhesion on various metal substrate surfaces after curing.

[0033] Furthermore, in the above step (3), the epoxy adhesive is applied in an amount of 400-500 g / m 2 The gluing process is to spray glue first and then scrape glue.

[0034] The further beneficial effect of adopting the above method is that by reasonably controlling the amount of epoxy adhesive, unnecessary waste can be reduced while ensuring product quality. By using glue spraying equipment, the deviation of the glue application amount can be accurately controlled within 0.5%, thereby accurately controlling the mixing ratio of component A and component B in the epoxy adhesive. At the same time, the glue application process of first spraying glue and then scraping glue is adopted to make the entire board surface evenly coated with epoxy adhesive. The present invention optimizes the glue application process of epoxy adhesive, improves the mixing uniformity of epoxy adhesive, the uniformity of glue application, and the stability of glue application amount.

[0035] Furthermore, in the above step (3), the compounding temperature is 30-35°C, the pressure is 2-3MPa, and the time is 12-16h.

[0036] The present invention also claims protection for an enamel composite board prepared by the preparation method.

[0037] The present invention also claims to protect the use of the enamel composite board prepared by the preparation method in interior decoration and curtain wall production.

[0038] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:

[0039] The enamel composite board of the present invention has excellent performance, and the bonding strength, weather resistance and flatness of the board are significantly improved. It is not only suitable for interior decoration, but also can be widely used in building curtain walls, thereby expanding its application range and improving its economic value. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 Schematic diagram of the structure of the enamel composite panel. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] In the following examples, the manufacturer of NPEL-128 is Nanya Electronic Materials (Kunshan) Co., Ltd., and the product batch number is 20230523;

[0043] The manufacturer of SL-102C-2 is Taizhou Hengchuang Insulation Materials Co., Ltd., and the product batch number is HC20230417;

[0044] Kaneka MZ100 is manufactured by Keneka and its batch number is MZ 22022;

[0045] The manufacturer of cardanol glycidyl ether is Shanghai Meidong Biotechnology Co., Ltd., and the product batch number is MD20230413;

[0046] The manufacturer of γ-glycidyl ether propyl triethoxysilane is Nanjing Shuguang Silane Chemical Co., Ltd., and the product batch number is 20230312S;

[0047] The manufacturer of Silok 7631 is Guangzhou Silok New Materials Co., Ltd., and the product batch number is 20;

[0048] The manufacturer of 800-mesh light calcium carbonate is Jiangxi Guangyuan Chemical Co., Ltd., and the product batch number is 20230610;

[0049] The manufacturer of Versamid 140 is GABRIEL, and the product batch number is V1002230201;

[0050] The manufacturer of R-2269 is Rich (Guangdong) Technology Co., Ltd., and the product batch number is R20230423;

[0051] The manufacturer of 2,4,6-tris(dimethylaminomethyl)phenol is EVONIK, and the product batch number is EK200323;

[0052] The manufacturer of 1500 mesh talcum powder is Jiangxi Guangyuan Chemical Co., Ltd., and the product batch number is 20230523.

[0053] Example 1

[0054] The preparation method of the enamel composite board specifically comprises the following steps:

[0055] (1) The enameled steel plate was sandblasted to a roughness of 1.5, glaze was sprayed to a thickness of 100 μm, high-temperature fired, stacked, and pre-pressed and shaped at a pressure of 2 MPa for 10 min;

[0056] (2) sandblasting the backing aluminum plate to a roughness of 1.5;

[0057] (3) The enameled steel plate, aluminum honeycomb core and backing aluminum plate are compounded using epoxy adhesive, and the amount of epoxy adhesive applied is 400g / m 2 The gluing process is to spray the glue first and then scrape the glue, the compounding temperature is 30℃, the pressure is 2MPa, and the time is 16h, and the enamel composite board is obtained;

[0058] The epoxy adhesive includes component A and component B, with a mass ratio of 2:1;

[0059] Component A per 100 g includes NPEL-128 30 g, SL-102C-2 30 g, kaneka MZ100 10 g, cardanol glycidyl ether 10 g, γ-glycidyl ether propyl triethoxysilane 4 g, Silok 763 11 g and 800 mesh light calcium carbonate 15 g;

[0060] Each 100 g of component B includes 40 g of Versamid 140, 20 g of R-2269, 4 g of 2,4,6-tris(dimethylaminomethyl)phenol, 11 g of Silok 763 and 35 g of 1500 mesh talc.

[0061] Example 2

[0062] The preparation method of the enamel composite board specifically comprises the following steps:

[0063] (1) The enameled steel plate was sandblasted to a roughness of 1.6, glaze was sprayed to a thickness of 120 μm, high-temperature fired, stacked, and pre-pressed and shaped at a pressure of 2.5 MPa for 10 min;

[0064] (2) sandblasting the backing aluminum plate to a roughness of 1.6;

[0065] (3) The enameled steel plate, aluminum honeycomb core and backing aluminum plate are composited using epoxy adhesive, and the amount of epoxy adhesive applied is 450g / m 2 The gluing process is to spray the glue first and then scrape the glue, the compounding temperature is 32℃, the pressure is 2.5MPa, and the time is 14h, and the enamel composite board is obtained;

[0066] The epoxy adhesive includes component A and component B, with a mass ratio of 2:1;

[0067] Component A per 100 g includes NPEL-128 30 g, SL-102C-2 30 g, kaneka MZ100 10 g, cardanol glycidyl ether 10 g, γ-glycidyl ether propyl triethoxysilane 4 g, Silok 763 11 g and 800 mesh light calcium carbonate 15 g;

[0068] Each 100 g of component B includes 40 g of Versamid 140, 20 g of R-2269, 4 g of 2,4,6-tris(dimethylaminomethyl)phenol, 11 g of Silok 763 and 35 g of 1500 mesh talc.

[0069] Example 3

[0070] The preparation method of the enamel composite board specifically comprises the following steps:

[0071] (1) The enameled steel plate was sandblasted to a roughness of 1.7, glaze was sprayed to a thickness of 150 μm, high-temperature fired, stacked, and pre-pressed and shaped at a pressure of 3 MPa for 10 min;

[0072] (2) The backing aluminum plate is sandblasted to a roughness of 1.7;

[0073] (3) The enameled steel plate, aluminum honeycomb core and backing aluminum plate are compounded using epoxy adhesive, and the amount of epoxy adhesive applied is 500g / m 2 The gluing process is to spray the glue first and then scrape the glue, the compounding temperature is 35℃, the pressure is 3MPa, and the time is 12h, and the enamel composite board is obtained;

[0074] The epoxy adhesive includes component A and component B, with a mass ratio of 2:1;

[0075] Component A per 100 g includes NPEL-128 30 g, SL-102C-2 30 g, kaneka MZ100 10 g, cardanol glycidyl ether 10 g, γ-glycidyl ether propyl triethoxysilane 4 g, Silok 763 11 g and 800 mesh light calcium carbonate 15 g;

[0076] Each 100 g of component B includes 40 g of Versamid 140, 20 g of R-2269, 4 g of 2,4,6-tris(dimethylaminomethyl)phenol, 11 g of Silok 763 and 35 g of 1500 mesh talc.

[0077] Performance Testing

[0078] 1. Determination of mixing ratio

[0079] The bonding surface of the selected material has no sandblasting, and the glue application amount is 350g / m 2 , curing conditions: 20℃, 12h, using traditional scraping process.

[0080] The test results are shown in Table 1.

[0081] Among them, the test basis standard for flat tensile strength is: GB / T1452-2005 (test method for flat tensile strength of sandwich structure); the test basis standard for roller peel strength is: GB / T1457-2005 (test method for roller peel strength of sandwich structure).

[0082] Table 1 Effect of mixing ratio on flat tensile strength and roller peel strength (average value)

[0083] Mixing ratio Flat tensile strength (MPa) Roller peel strength (N.mm / mm) 2:0.9 0.80 30 2:0.95 1.05 32 2:1 1.2 36 2:1.05 1.12 33 2:1.1 0.84 33

[0084] It can be seen from Table 1 that when the mass ratio of component A to component B in the epoxy adhesive is 2:1, the flat tensile strength and roller peel strength reach the optimal state, indicating that precise control of the amount of glue applied plays a relatively important role.

[0085] 2. Determination of sizing process

[0086] The mass ratio of component A to component B in the epoxy adhesive is 2:1. The bonding surface of the selected material has no sandblasting, and the amount of adhesive applied is 350g / m 2 , curing conditions: 20℃, 12h.

[0087] The test results are shown in Table 2.

[0088] Table 2 Effect of sizing process on flat tensile strength and roller peel strength (average value)

[0089]

[0090] As shown in Table 2, under the glue spraying method, the values ​​of flat pull strength and roller peel strength are relatively uniform, but generally low. Under the glue scraping method, the values ​​of flat pull strength and roller peel strength fluctuate greatly. Under the glue spraying + glue scraping method, the values ​​of flat pull strength and roller peel strength are relatively uniform, and the strength is guaranteed.

[0091] 3. Determination of glue application amount

[0092] The mass ratio of component A to component B in the epoxy adhesive is 2:1. The bonding surface of the selected material has no sandblasting. The curing conditions are: 20°C, 12h, and the glue spraying + scraping process is adopted.

[0093] The test results are shown in Table 3.

[0094] Table 3 Effect of glue application amount on flat tensile strength and roller peel strength (average value)

[0095] <![CDATA[施胶量(g / m 2 )]]> Flat tensile strength (MPa) Roller peel strength (N.mm / mm) 300-350 1.11 30 350-400 1.32 38 400-450 1.51 44 450-500 1.63 44 500-550 1.62 43 550-600 1.62 45

[0096] It can be seen from Table 3 that the glue application amount is 500g / m 2 When the glue amount is within 500g / m 2 When the pressure is above 400 g / m, the increase of flat tensile strength and roller peeling strength is not obvious. Therefore, the glue application amount is determined to be 400-500 g / m 2 .

[0097] 4. Determination of roughness

[0098] The mass ratio of component A to component B in the epoxy adhesive is 2:1. The curing conditions are 20°C, 12h, and the glue spraying + scraping process is adopted. The glue application amount is 400-500g / m 2 .

[0099] The test results are shown in Table 4.

[0100] Table 4 Effect of roughness on flat tensile strength and roller peel strength (average value)

[0101]

[0102] It can be seen from Table 4 that the increase in the roughness of the bonding surface of the enameled steel plate and the backing aluminum plate has a significant promoting effect on the improvement of the flat tensile strength and the roller peeling strength, but the increase in roughness will invisibly increase the manufacturing cost. Considering the comprehensive performance, a roughness of 1.5-1.7 is feasible.

[0103] 5. Determination of pressure and time

[0104] The mass ratio of component A to component B in the epoxy adhesive is 2:1. The roughness of the bonding surface of the selected material is 1.5-1.7. The curing conditions are: 20℃, 12h, and the glue spraying + scraping process is adopted. The glue application amount is 400-500g / m 2 .

[0105] The test results are shown in Table 5.

[0106] Table 5 Effect of pressure and time on the flatness of the plate after pre-pressing and compounding

[0107]

[0108] It can be seen from Table 5 that the greater the pre-pressing pressure, the longer the holding time, the smaller the deformation, the flatter the plate, and the plate pressure is 2-3MPa and the time is 10min to achieve the required flatness.

[0109] 6. Performance test of enamel composite board

[0110] The enamel composite panel prepared in Example 2 was taken and applied to an exterior curtain wall, and its salt water resistance, acid resistance, alkali resistance, adhesion, hard object impact resistance, soft heavy object impact resistance, combustion performance A and temperature difference resistance were tested respectively.

[0111] The test results are shown in Table 6.

[0112] Table 6 Performance test results of exterior curtain wall enamel composite panels

[0113]

[0114]

[0115] It can be seen from Table 6 that, through strict inspection and testing, the performance and safety performance of the exterior curtain wall enamel composite panel of the present invention are relatively excellent in various harsh environments.

[0116] The above tests show that the enamel composite panel of the present invention has excellent performance, and the bonding strength, weather resistance and flatness of the panel are significantly improved. It is not only suitable for interior decoration, but also can be widely used in building curtain walls, thereby expanding its application range and improving its economic value.

[0117] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing an enamel composite panel, characterized in that: The specific steps include: (1) The enameled steel plate is sandblasted, sprayed with glaze, fired at high temperature, stacked, and pre-pressed; (2) sandblasting the backing aluminum plate; (3) The enameled steel plate, the aluminum honeycomb core and the backing aluminum plate are compounded in sequence using an epoxy adhesive to obtain the enameled composite plate.

2. The method for preparing a vitreous enamel composite board according to claim 1, characterized in that: In step (1), the sandblasting is performed until the roughness of the enameled steel plate is 1.5-1.

7.

3. The method for preparing a vitreous enamel composite board according to claim 1, characterized in that: In step (1), the spraying thickness of the glaze is 100-150 μm.

4. The method for preparing a vitreous enamel composite board according to claim 1, characterized in that: In step (1), the pre-pressing and shaping pressure is 2-3 MPa and the time is more than 10 minutes.

5. The method for preparing a vitreous enamel composite board according to claim 1, characterized in that: In step (2), the sandblasting is performed until the roughness of the backing aluminum plate is 1.5-1.

7.

6. The method for preparing a vitreous enamel composite board according to claim 1, characterized in that: In step (3), the epoxy adhesive comprises component A and component B in a mass ratio of 2:1; In terms of mass percentage, the component A comprises 30%-40% epoxy resin, 30%-40% modified epoxy toughening agent, 5%-10% core-shell toughening particles, 5%-10% active diluent, 1%-5% silane coupling agent, 0.5%-1% wetting dispersant and 15%-25% filler; In terms of mass percentage, the B component includes 30%-40% polyamide, 10%-20% modified amine, 1%-5% accelerator, 0.5%-1% wetting and dispersing agent and 30%-40% filler; The epoxy resin is at least one of NPEL-128, EPOKUKDO YD-128, NPEF-170, YDF-170, DEN 431 and NPPN 631; The modified epoxy toughening agent is at least one of SL-102C-2, 102C-4H, 102C-4L, 102C-4T, 102C-4R, PD3604, PD3614, JEF-0211 and ERS-172; The core-shell toughened particles are at least one of kaneka MZ100, kaneka MZ200, kaneka B-564 and kaneka M-701; The active diluent is at least one of 1.4-butanediol diglycidyl ether, 1.6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, cardanol glycidyl ether and pentaerythritol tetraglycidyl ether; The silane coupling agent is γ-glycidyl ether propyl triethoxy silane; The wetting and dispersing agent is at least one of BYK-2151, BYK-163, EFKA-4010 and Silok 7631; The filler is at least one of 150 mesh heavy calcium carbonate, 800 mesh light calcium carbonate, 1500 mesh talc, fumed silica and kaolin; The polyamide is at least one of Versamid 140, WSCM-4140, D8140, Ancamide 2784, G-640, G-0930 and G-5022; The modified amine is at least one of LT-477, SF-PAA-5035P, SF-PAA-4530, R-2269 and R-3611; The accelerator is at least one of 2,4,6-tris(dimethylaminomethyl)phenol, 2-ethyl-4-methylimidazole, salicylic acid, triphenylphosphine and 1,8-diazabicycloundec-7-ene.

7. The method for preparing a vitreous enamel composite board according to claim 1, characterized in that: In step (3), the epoxy adhesive is applied in an amount of 400-500 g / m 2 The gluing process is to spray glue first and then scrape glue.

8. The method for preparing a vitreous enamel composite board according to claim 1, characterized in that: In step (3), the compounding temperature is 30-35° C., the pressure is 2-3 MPa, and the time is 12-16 h.

9. An enamel composite board prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the enamel composite panel prepared by the preparation method according to any one of claims 1 to 8 in interior decoration and curtain wall production.

Citation Information

Patent Citations

  • Modified epoxy adhesive and preparing method thereof

    CN106433537A

  • Thermal shaping system and thermal shaping method

    CN110860581A

  • Preparation method of cast iron enamel pot with antibacterial function and cast iron enamel pot

    CN115778166A

  • Boiling-resistant odor-removing antibacterial enamel glaze as well as preparation method and application thereof

    CN119019094A

  • Energy-saving heat-insulation enameled pressed steel curtain wall

    CN202416634U

Cited By

  • Architectural ceramic enhanced by using graded waste ceramic powder and preparation method thereof

    CN121651872A